2003
DOI: 10.1007/s00402-003-0514-z
|View full text |Cite
|
Sign up to set email alerts
|

Stress fractures of the femoral neck and coxa vara

Abstract: It is suggested that coxa vara predisposes to femoral neck stress-fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…This could possibly explain the particular fracture orientation observed on the two patients' radiographs, and the absence of previously reported histological features (12). A differential diagnosis would be the stress fractures reported to occur in femurs with coxa vara (13); however in each case, both hips looked symmetric, the contralateral neck-shaft angles measured more than the conventional cut-off for coxa vara, and the fracture lines were smooth and near-vertical.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 77%
“…This could possibly explain the particular fracture orientation observed on the two patients' radiographs, and the absence of previously reported histological features (12). A differential diagnosis would be the stress fractures reported to occur in femurs with coxa vara (13); however in each case, both hips looked symmetric, the contralateral neck-shaft angles measured more than the conventional cut-off for coxa vara, and the fracture lines were smooth and near-vertical.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 77%
“…Genetic factors may play a role in the development of stress fractures in individuals subjected to heavy exercise and mechanical loading [5]. Also stress fracture of the femoral neck in active adults is known to be related with coxa vara [1]. Biomechanically, direct muscle pulling effect increases in coxa vara and leads to fatigue of opposing muscle group.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical effect by FAI mechanism in abnormal orientation of acetabulum and deep socket may predispose to development of stress fracture of femoral neck. Carpintero et al [1] reported coxa vara, a form of cam impingement, is possibly related with stress fracture of femoral neck. There was a normal neck-shaft angle (128 in degree) and no abnormal head-neck offset in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because insufficiency stress fractures are associated with decreased bone mineral density, 37 they tend to be most common in the elderly, especially postmenopausal women. 56 Other predisposing factors for poor bone density include radiation treatments, 44 rheumatoid arthritis due at least in part to the associated disuse and either corticosteroid or methotrexate treatment, 39 renal failure, 52 coxa vara, 13 metabolic disorders, and Paget's disease. 16,40,59 FIGURE 1.…”
mentioning
confidence: 99%